(untitled) (Global Journals of Research in Engineering, 2013)
Long haul multichannel optical communication system is extremely affected by crosstalk due to Four wave mixing (FWM). The FWM effect depends on channel separation and number of channels. The paper presents the design and performance analysis of FWM effect on bit error rate, Q-factor, output spectrums and eye opening by varying channel spacing and number of channels. Results show that FWM effect reduces with increase in channel spacing and decrease in number of channels. Further it can be reduced by unequal channel spacing.